ANTI-ACNE GEL OF ISOTRETINOIN: FORMULATION AND EVALUATION - Nikam, Shreya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Isotretinoin is a very effective drug in the treatment of acne vulgaris by topically. The objective of present study was formulation development of anti-acne gel using Isotretinoine and span 80 for topical delivery to cure nodulosystic acne vulgaris. Furthermore, the comparative study of all the evaluation parameters done with marketed formulation of same drug. Methods: Formulation of anti-acne gel of isotretinoin using Carbopol 940 as a polymer and incorporating isotretinoin in form of topical semi-solid gel using magnetic stirrer, Cremophor RH 40, and butylated hydroxytoluene. Drug was uniformly dispersed in Cremophor RH 40 and the respected solvents. Ethanol, isopropyl alcohol, and glycerin were used as solvents in 15% quantity. Further, the formulation was evaluated for physicochemical evaluation of gel formulations. The prepared gel were optimized statistically and characterized for pH, spredability, drug content, viscosity, in vitro diffusion study, acute skin irritation test, and antimicrobial activity. Evaluation test was also compared with marketed formulation of isotretinoin, that is, Sortet gel. The antibacterial and anti-acne activity of different formulations was determined by modified agar well diffusion method on the culture of Propionibacterium acne also compared with marketed formulation. Results: The optimized batch (B10) showed highest spreadability (32.422 g/cm3) in all formulations and also have high percentage of drug contents (95.60%). The spreadability value was 17.998 g/cm3 showing good spreadability. The viscosity of optimized batch was observed less as compared to other formulations, ultimately showed releases also more. In the in vitro diffusion study, B10 batch release 85.69% of the drug as compared to Sotret gel. The antibacterial activity was studied on anaerobic microorganism P. acne, compared with marketed Sortet gel. Optimized batch showed maximum zone of inhibition to P. acne below marketed formulations and standard benzyl peroxide gel. Conclusion: The topical anti-acne gel of isotertinoin was successfully formulated and evaluated for different parameters. The results indicate that the active component, that is, isotertinoin is more effective when subjected in gel formulations and produces effective anti-acne activity in the management of nodulosystic acne vulgaris.